Sosialisasi dan Pelatihan Pengelolaan Sampah Home Industry Berbasis Partisipatif di Desa Munggu Kecamatan Mengwi Kabupaten Badung - I Made Suwitra Wirya; Ni Nyoman Rusmiati; I Ketut Budiasa; Sulistyo Adi Joko Saharjo; Ni Luh Sili Antari; Tiara Kusuma Dewi; Made Dwipa Negara; I Made Sudirman; Yohanes Imanuel Budi Hutomo (Prosiding Seminar Nasional Riset dan Pengabdian pada Masyarakat, 2024)
This research aims to improve environmental quality and create a friendly and healthy environment in Munggu Village, Mengwi District, Tabanan Regency. However, in practice, this goal has not been successfully achieved. The research employs a qualitative descriptive approach, with data collection techniques including participatory observation and structured interviews with participants and activity organizers. One of the causes of deteriorating environmental quality is waste. Improper waste disposal can lead to various problems for the community and the environment, such as public health issues, environmental pollution, and soil contamination, which may result in disasters. The lack of proper waste disposal is caused by a lack of awareness and knowledge of waste management among the community and insufficient attention from stakeholders to the waste management system. Munggu Village is a rural residential area with potential for sustainable local industry. However, this residential area still lacks a proper waste management system. The results of this activity indicate that waste management in home industries in Munggu Village can be carried out by understanding the types of waste, methods of separating each type of waste, waste management systems, and the benefits of processing waste into useful products.